2015
DOI: 10.4103/0974-9233.167827
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of meibomian gland dysfunction in patients with diabetes

Abstract: Aims of the Study:To study the frequency of meibomian gland dysfunction (MGD) in patients of diabetes mellitus with dry eye.Materials and Methods:A case-control cross sectional study.Sampling:Purposive random sampling. Totally, 200 eyes of 100 patients of diabetes mellitus and an equal number of eyes of normal subjects as control, who were gender and age matched and all of whom were symptomatic for dry eye were assessed for MGD by noting the symptoms and determining the meibomian gland expression scale for vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 14 publications
1
7
2
Order By: Relevance
“…We compared meibographic findings in the 4 groups, and a significant difference in the meiboscore was found between the control patients and the over 10 years diabetic patients. This was consistent with previous findings [ 23 , 24 ] where diabetes was associated with MGD. Our data showed that duration of diabetes was closely related to the severity of meibomian gland abnormality (as reflected by the meiboscore, which indicates meibomian gland loss).…”
Section: Discussionsupporting
confidence: 94%
“…We compared meibographic findings in the 4 groups, and a significant difference in the meiboscore was found between the control patients and the over 10 years diabetic patients. This was consistent with previous findings [ 23 , 24 ] where diabetes was associated with MGD. Our data showed that duration of diabetes was closely related to the severity of meibomian gland abnormality (as reflected by the meiboscore, which indicates meibomian gland loss).…”
Section: Discussionsupporting
confidence: 94%
“…Accordingly, several studies documented that diabetes mellitus was associated with MGD [22, 33]. Surprisingly, we found no association of MGL with systemic diseases such as diabetes mellitus, after adjusting for age and sex.…”
Section: Discussioncontrasting
confidence: 71%
“…These structures regulate tear secretion and formation of the tear film to maintain the integrity and normal function of the tear film. Abnormality in any part of ocular surface tissues could result in xerophthalmia (Malik et al, 2013;Shamsheer and Arunachalam, 2015). Diabetic patients often show incomplete conjunctival epithelium, which leads to difficulties in tear film attachment and a reduction in the numbers of goblet cells.…”
Section: Discussionmentioning
confidence: 99%